2006
DOI: 10.1007/s10750-005-1604-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Elevated Velocity and Sediment Abrasion on Benthic Algal Communities

Abstract: Of the mechanisms that remove benthic algae during flood disturbances, relatively little is known about the effects of sediment scour. We investigated suspended sediment scour using naturally colonized benthic algal communities exposed to realistic velocities and suspended sediment concentrations in a laboratory flowtank. Increased velocity alone removed benthic algal biomass, and high suspended sediment concentrations further increased algal removal. Efficacy of biomass removal by velocity and suspended sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 38 publications
2
71
0
2
Order By: Relevance
“…alteration of body posture, to the increased flow velocity (Lancaster, 1999). The decrease in the biomass of benthic algae may be due to abrasion or scouring (Francoeur and Biggs, 2006). Overall, our experiments showed that an increase in flow velocity from 2.9 to 6.9 cm s À 1 may lead to removal of some algae, drift of some invertebrates, but most macroinvertebrates will be able to cope with the increased flow by, for example, adjustments of body posture.…”
Section: Effects Of Flow Increase and Nutrients On Leaf Litter Degradmentioning
confidence: 66%
“…alteration of body posture, to the increased flow velocity (Lancaster, 1999). The decrease in the biomass of benthic algae may be due to abrasion or scouring (Francoeur and Biggs, 2006). Overall, our experiments showed that an increase in flow velocity from 2.9 to 6.9 cm s À 1 may lead to removal of some algae, drift of some invertebrates, but most macroinvertebrates will be able to cope with the increased flow by, for example, adjustments of body posture.…”
Section: Effects Of Flow Increase and Nutrients On Leaf Litter Degradmentioning
confidence: 66%
“…One of the Correspondence to: Laura Virtanen. E-mail: Laura.Virtanen@ helsinki.fi most significant factors leading to a decrease of algal biomass is physical disturbance (Steinman & McIntire, 1990;Stevenson et al, 1996), through substratum instability and associated abrasion, high water velocities, and abrasion by suspended sediments (Francoeur & Biggs, 2006). In addition, biotic factors, such as grazing by invertebrates and fish, may affect diatom occurrence (Feminella & Hawkins, 1995;Stevenson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As características microambientais, entretanto, não apresentaram grande variação entre as estações do ano, com exceção da velocidade da correnteza, bem mais elevada no verão. A velocidade do fluxo de água é um fator bastante importante na distribuição de macroalgas lóticas (Reiter & Carlson 1986, Biggs et al 1998, Francoeur & Biggs 2006. A alta velocidade da correnteza pode exercer pressão negativa sobre os organismos aderidos, sendo que poucas espécies são capazes de suportar a força da correnteza, que muitas vezes carreia grande parte da comunidade.…”
Section: Discussionunclassified
“…Isto mostra que, mesmo em um ambiente que apresente certo grau de heterogeneidade espacial, quando uma das condições altera-se em maior escala, a comunidade também sofre as consequências modificando seu padrão de distribuição. Os maiores valores de abundância e dominância verificados no período de verão reforçam tal constatação, onde as poucas espécies mais bem adaptadas ao fluxo da correnteza mais elevado predominam e abundam sobre as demais (Francoeur & Biggs 2006 (Borges & Necchi Júnior 2006). Durante o período de inverno, a redução da velocidade da correnteza foi o fator responsável pelo aumento da diversidade de espécies.…”
Section: Discussionunclassified